The influencing factors of online banking fraud awareness in UTAR Kampar - Chin, Ke Li; Tan, Xin Tong; Tang, Jia Hooi; Toh, Khai Li (2023)
As the use of online banking becomes more widespread, the frequency of online banking fraud is also on the rise. The purpose of this research is to examine the factors that impact consumers' awareness towards online banking fraud. To gather information for this study, questionnaires were given to 400 UTAR Kampar students between the ages of 18 and 24 by using the convenient non-random sampling. The questionnaire assessed participants' levels of understanding about online banking fraud related to the relationship between personal financial distress, empathy, attitude towards fraud and knowledge of online banking. In this study, several analysis tests have been used to analyze the hypothesis such as descriptive analysis, scale measurement, preliminary data screening and inferential analysis. The outcomes of this research are significant for financial institutions and policymakers as they work to combat online banking fraud. In the future, this study will draw attention to new paradigms that will be useful for discussions of the online fraud trend and could contribute to a more comprehensive analysis.